Negotiating pleasure and sexual risk: Alcohol use among female university students - Shakila Singh (Transformation in Higher Education, 2025)
This study explores how female university students navigate the interplay between the pleasure that alcohol gives them and the risks to their sexual safety it poses. This mixed-method study employed an open-ended questionnaire administered by a student-researcher. The sample comprised 76 voluntary female students who reported consuming alcohol. The findings indicate that women who consume alcohol exercise personal agency in their self-expression, yet they do so within a context of gender and sexual violence. Participants articulated various strategies for mitigating risks to their sexual safety while drinking, such as consuming alcohol within supportive social networks, avoiding financial dependence, and regulating their alcohol intake.